Atrial fibrillation diagnosis by a systematic 14-day continuous ECG-Holter in patients with high cardiovascular risk and clinical palpitation: the prospective AFTER study. (3rd October 2022) - Halimi, F; Sabouret, P; Huberman, J P; Cohen, S; Ouazana, L; Hoffman, O; Assouline, S; Guedj-Meynier, D; Schwartz, J; Weiss, P; Lafont, C; Lellouche, N
Abstract: Background: Atrial Fibrillation (AF) is asymptomatic in 20–30% of cases. New technologic tools for continuous ECG monitoring have been developed to detect and potentially treat AF in specific population with high cardiovascular risk. Purpose: We aimed to evaluate the prevalence and the management of AF diagnosed in patients with no previous documented AF but with a high cardiovascular risk and clinical palpitation undergoing systematic 14-day continuous ECG-Holter monitoring and associated characteristics. Methods: Patients were prospectively enrolled from December 2019 to December 2021 in this multicentered study, sponsored by the French National College of Cardiology. Patients needed to meet the following criteria: CHA2DS2VASc score ≥3 in women >2 in men associated with clinical palpitation without previous documented arrhythmia, particularly AF. Exclusion criteria were: previous documented AF, participation to another study that could interfere with the current study, pregnancy, previous skin intolerance to ECG-Holter electrodes. Included patients underwent a 14-day monitoring Holter-ECG to detect cardiac arrhythmia, particularly AF. Patients' characteristics, type of arrythmias and management of detected AF were described. Results: Among the 336 included patients, 39% were men, median age was 73 [64.5–78] years, 71.5% had hypertension and 46.5% had a previous history of stroke. AF was detected in 14% of patients, among which 23.4% in the first 24 hours monitoring. In univariate analyses, older age (p=0.045) was significantly associated with AF, and a trend was observed regarding male gender (p=0.067) and less antiplatelet therapy (p=0.058). Patients with diagnosed AF had a prescription of anticoagulation therapy in 90% of cases consisting in apixaban and rivaroxaban for 72% and 28% respectively. Antiarrhythmic drugs were administered in 90% of AF patients and 13% underwent AF ablation. Conclusions: The systematic AF screening of selected patients based on CHA2DS2VASc score ≥3 in women >2 in men associated with palpitations allows to diagnose AF in 14% of the population with a 14-day continuous ECG-Holter. This strategy seems efficient as it induced the prescription of anticoagulation and antiarrhythmic therapy in 90% of individuals. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): NATIONAL COLLEGE OF FRENCH CARDIOLOGISTS